Nation, State and Territorial Unity : a Trans-Outaouais View - Burghardt, Andrew (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1980)
The concept of "nation" is currently being applied on more than one level. Whereas many Québécois maintain that a nation should be a state, world experience shows many nations as forming constituent parts of larger-scaled nations. Sovereignty must be seen as having priority over "association". A secession of Québec would split Canada into at least three portions, and would cause a reorientation of the remnant pieces away from the centre. Several potential boundary problems would exist. The recent development of a Canadian nationalism should not be overlooked.